Tinjauan Yuridis Tindak Pidana Pemalsuan Surat Keterangan Sahnya Hasil Hutan Kayu (Studi Putusan No. 58/Pid.B/2022/Pn.Sdr) - Esa, Ambo (Universitas Islam Negeri Alauddin Makassar, 2023)
The aim of the research is to find out the application of material law to decisions no. 58/Pid.B/2022/PN.Sdr and to find out what the judges' considerations are in making a decision against the perpetrators of the crime of forging letters. This type of research is normative. The results of this study indicate that: (1) In the application of Law Number 18 of 2013 concerning Prevention and Eradication of Forest Destruction in its decision, the public prosecutor used a combination of charges, and this practice is appropriated with the existing regulations; (2) Based on the judge's consideration referring to Article 88 paragraph (1) letter